Solid-state battery and its manufacturing method by protonation

The method of protonating ceramic bodies in solid-state batteries improves contact between the anode and the solid electrolyte, reducing dendrite formation and short circuits, thereby enhancing the battery's performance and safety.

JP7664961B2Active Publication Date: 2025-04-18THE SWATCH GRP RES & DEVELONMENT LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023057168
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-04-08
Filing Date
2023-03-31
Publication Date
2025-04-18
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

Solid-state batteries face challenges in achieving effective contact between the anode and the solid electrolyte, leading to issues like lithium dendrite formation and short circuits, which are not adequately addressed by the use of liquid electrolytes.

Method used

A method for producing solid-state batteries involves protonating a ceramic body to create a softer protonated layer, which allows for improved contact with metal elements forming the negative electrode, and an aprotonated portion that prevents dendrite propagation and short circuits.

Benefits of technology

The method enhances the contact area between the metal element and the solid electrolyte, reducing the risk of lithium dendrite formation and short circuits, while maintaining the stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664961000001
    Figure 0007664961000001
  • Figure 0007664961000002
    Figure 0007664961000002
  • Figure 0007664961000003
    Figure 0007664961000003
Patent Text Reader

Abstract

To provide a method for producing a solid-state battery, which improves the contact between an anode and a solid electrolyte, without the use of a liquid contact element.SOLUTION: The present invention relates to a solid-state battery (20) including a solid electrolyte (8) and a production method thereof. The method includes the following successive steps: a step (1) of protonating a body (11) containing, preferably being entirely made of, a protonatable ceramic material, to form a protonated layer (12, 13) on the body (11); a step (4) of depositing a metal element forming an anode (14) on the protonated layer (13) on a first side (7) of the body (11); a step (5) of assembling a cathode (15) on a second side (9) of the body (11), preferably opposite the first side (7) of the anode (14); and a step (6) of forming dendrites (18) from the metal element in the protonated layer (13) of the body (11).SELECTED DRAWING: Figure 2f
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to solid-state batteries, and also to "all-solid-state batteries".

[0002] The present invention further relates to a method for producing such a solid-state battery.

[0003] The invention further relates to an electronic system, such as a watch, a laptop computer, a mobile phone or an automobile, that includes such a solid-state battery. [Background technology]

[0004] Solid-state or all-solid-state batteries are an alternative to lithium-ion batteries. Unlike lithium-ion batteries, which contain a liquid electrolyte, solid-state batteries have a solid electrolyte between the anode and cathode.

[0005] Such batteries have the advantage of having a higher energy density and therefore a larger storage capacity than lithium-ion batteries, which makes them promising for many applications.

[0006] Ceramic compounds such as LLZO compounds are known for use as solid electrolytes.

[0007] LLZO-based compounds have high ionic conductivity. These ceramic compounds contain lithium, lanthanum, zirconium, and oxygen, and have the chemical formula Li7La3Zr2O 12 or Li7La3Zr2O7. It can also be doped with tantalum or aluminum to stabilize these cubic phases that are conductive to lithium ions. 6.4 La3Zr2Ta 0.6 O 12 has.

[0008] One of the drawbacks of ceramic compounds is the contact between the negative electrode, for example made of lithium, and the solid electrolyte. More specifically, it is important to prevent impurities and irregularities between the two elements, since their presence can lead to current crowding and cavities, which can lead to the formation of lithium dendrites that can pass through the ceramic compound and cause a short circuit. This is because these current crowding can exceed a current threshold, which then leads to the formation of dendrites in the ceramic compound, especially lithium dendrites.

[0009] One solution to this problem is to place a conductive liquid between the ceramic compound and the lithium anode, which improves contact between the two.

[0010] However, problems arise with batteries containing liquid electrolytes, in particular the risk of the liquid leaking out of the battery and the consequences that accompany it, and even the presence of liquid does not completely avoid the risk of lithium dendrite formation. Summary of the Invention [Problem to be solved by the invention]

[0011] The object of the present invention is to overcome the aforementioned drawbacks and aims to provide a method for producing a solid-state battery that improves the contact between the negative electrode and the solid electrolyte without the use of liquid contact elements. [Means for solving the problem]

[0012] Therefore, the present invention relates to a method for producing a solid-state battery.

[0013] The present invention is notable in that the method comprises the following successive steps: - protonating a body containing, preferably consisting entirely of, a protonatable ceramic material to form a protonated layer on the body; - depositing a metallic element forming a negative electrode on the protonated layer on the first side of the body; - attaching a positive electrode to a second side of the body, preferably opposite the first side of the negative electrode; and - forming dendrites from metal elements in the protonated layer of the body.

[0014] The protonated layer of the ceramic is softer than the original ceramic, so dendrites are more likely to form in this layer. The dendrites improve the contact between the metal elements and the body of the solid electrolyte, especially since the dendrites increase the contact area by making the contact irregular. In addition, the remaining non-protonated part of the body is harder, which prevents these dendrites from propagating to the positive electrode and causing a short circuit. Furthermore, it prevents the risk of current crowding and therefore the risk of dendrites forming in this non-protonated part.

[0015] According to a particular embodiment of the invention, the ceramic material is selected from: - doped or undoped lithium and / or lanthanum zirconium oxides of the LLZO system, - doped or undoped β-alumina solid electrolyte materials of the Na-b''-Al2O3 system; - ternary or quaternary or higher sulfide-based solid electrolyte materials, for example of the Li6PS5X system (X being selected from the elements Cl, Br or I) or the Li2S-P2S5 system, - Ternary or quaternary or higher halogen-based solid electrolyte materials, for example, Li3MX6-based (where M is a metal or metal alloy and X is a halogen); - LISICON (lithium superionic conductor) system, e.g. Li 4±x S 1-x X x Lithium ion conducting solid electrolyte materials based on O4 (X is selected from the elements P, Al, or Ge), and - NASICON (sodium superionic conductor) system, e.g. Na x A sodium ion conducting solid electrolyte material in the MM'(XO4)3 system (wherein M and M' are metals and X is selected from the elements Si, P, or S).

[0016] According to certain embodiments of the invention, the protonation step involves immersing the body in a protic or acidic solvent, such as water, acetone, mineral oil, or ethanol.

[0017] According to a particular embodiment of the invention, the method includes an additional step of heating the body to a predetermined temperature to remove impurities from the body, the predetermined temperature being preferably between 350 and 450°C, and the additional heating step precedes the step of depositing the metallic element.

[0018] According to a particular embodiment of the present invention, the dendrite formation step involves repeated successive current flow cycles between the negative and positive electrodes.

[0019] According to a particular embodiment of the invention, the metal elements are melted onto the body during the metal element deposition step.

[0020] According to a particular embodiment of the invention, the metallic element comprises a material selected from the following: - Alkali metals such as lithium, sodium, potassium, rubidium, cesium, or francium, - alkaline earth metals such as beryllium, magnesium, calcium, strontium, barium, or radium, - all transition metals from groups 3 to 11 of the periodic table, including the lanthanides and actinides, - Alloys of these metals.

[0021] According to certain embodiments of the invention, the method includes the additional step of removing a portion of the protonated layer from the body in order to laminate the positive electrode directly onto the non-protonated portion of the body.

[0022] According to a particular embodiment of the invention, the additional step of removing a portion of the protonated layer from the body is performed by polishing the second side of the body.

[0023] According to a particular embodiment of the invention, the positive electrode contains a material selected from the following: - LiNi x Mn y Co z O2 or Li 2-x-y-z Ni x Mn y Co z Lithium nickel manganese cobalt oxide (NMC) such as O2, where x+y+z≦1, - LiNi 0.5 Mn 1.5 Lithium nickel manganese oxide (LNMO) such as O4, - Lithium iron phosphate (LFP) such as LiFePO4, - LMO-based lithium manganates such as LiMn2O4, and - NCA-based lithium nickel cobalt aluminum oxides such as LiNiCoAlO2.

[0024] The present invention further relates to a solid-state battery comprising an anode, a cathode, and a ceramic solid electrolyte, the solid electrolyte having a protonated layer and a non-protonated portion superimposed thereon, the cathode being laminated on a body, the anode comprising a metallic element laminated on the protonated layer of the body opposite the positive electrode, the metallic element comprising a dendrite infiltrated into the protonated layer of the body.

[0025] According to a particular embodiment of the invention, the dendrites are blocked by non-protonated parts of the body.

[0026] According to a particular embodiment of the invention, the metallic element comprises a material selected from the following: - Alkali metals such as lithium, sodium, potassium, rubidium, cesium, or francium, - alkaline earth metals such as beryllium, magnesium, calcium, strontium, barium, or radium, - all transition metals from groups 3 to 11 of the periodic table, including the lanthanides and actinides, - Alloys of these metals.

[0027] According to a particular embodiment of the invention, the ceramic material is selected from: - doped or undoped lithium and / or lanthanum zirconium oxides of the LLZO system, - doped or undoped β-alumina solid electrolyte materials of the Na-b''-Al2O3 system; - ternary or quaternary or higher sulfide-based solid electrolyte materials, for example of the Li6PS5X system (X being selected from the elements Cl, Br or I) or the Li2S-P2S5 system, - Ternary or quaternary or higher halogen-based solid electrolyte materials, for example, Li3MX6-based (where M is a metal or metal alloy and X is a halogen); - LISICON (lithium superionic conductor) system, e.g. Li 4±x S 1-x X x Lithium ion conducting solid electrolyte materials based on O4 (X is selected from the elements P, Al, or Ge), and - NASICON (sodium superionic conductor) system, e.g. Na x A sodium ion conducting solid electrolyte material in the MM'(XO4)3 system (wherein M and M' are metals and X is selected from the elements Si, P, or S).

[0028] According to a particular embodiment of the invention, the positive electrode is attached to the unprotonated portion of the body.

[0029] According to a particular embodiment of the invention, the positive electrode contains a material selected from the following: - LiNi x Mn y Co z O2 or Li 2-x-y-z Ni x Mn y Co z Lithium nickel manganese cobalt oxide (NMC) such as O2, where x+y+z≦1, - LiNi 0.5 Mn 1.5 Lithium nickel manganese oxide (LNMO) such as O4, - Lithium iron phosphate (LFP) such as LiFePO4, - LMO-based lithium manganates such as LiMn2O4, and - NCA-based lithium nickel cobalt aluminum oxides such as LiNiCoAlO2.

[0030] The invention further relates to an electronic system comprising such an all-solid-state battery, such as a watch, a drone, a laptop computer, a mobile phone, or an automobile.

[0031] Other specific features and advantages will be clearly observed in the following description, given as a general guide and in no way as a limiting guide, with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0032] [Figure 1] FIG. 2 is a block diagram showing steps of the method according to the present invention; [Figure 2a] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2b] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2c] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2d] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2e] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2f] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] The present invention relates to a method 10 for producing a solid-state battery 20. Such a battery 20 includes an anode 14, a cathode 15, and an electrolyte disposed between the cathode 15 and the anode 14. Solid-state electrolyte 8 is understood to refer to an electrolyte that is not a liquid.

[0034] The electrolyte 8 is formed from a body 11 containing a material that can be protonated. + It is possible to perform ion exchange, and preferably the body 11 is made entirely of this material.

[0035] The ceramic material used can be selected from the following: - doped or undoped lithium and / or lanthanum zirconium oxides of the LLZO system, - doped or undoped β-alumina solid electrolyte materials of the Na-b''-Al2O3 system; - ternary or quaternary or higher sulfide-based solid electrolyte materials, for example of the Li6PS5X system (X being selected from the elements Cl, Br or I) or the Li2S-P2S5 system, - Ternary or quaternary or higher halogen-based solid electrolyte materials, for example, Li3MX6-based (where M is a metal or metal alloy and X is a halogen); - LISICON (lithium superionic conductor) system, e.g. Li 4±x S 1-x X x Lithium ion conducting solid electrolyte materials based on O4 (X is selected from the elements P, Al, or Ge), and - NASICON (sodium superionic conductor) system, e.g. Na x A sodium ion conducting solid electrolyte material in the MM'(XO4)3 system (wherein M and M' are metals and X is selected from the elements Si, P, or S).

[0036] The ceramic material is preferably made entirely of this material.

[0037] Preferably, LLZO based compounds are selected because they have high ionic conductivity.

[0038] To produce the battery 20, a method is used that includes a first step 1 of protonating the ceramic body 11. To replace the atoms of the ceramic with protons, the body 11 is immersed in a protic or acidic solvent, such as water, acetone, mineral oil, or ethanol. Preferably, water is selected as the protic solvent.

[0039] Body 11 is soaked for an extended period of time, at least a day, preferably several days, or a week or more, depending on the size of body 11 and the desired protonated layer.

[0040] The body is shaped as a pellet, for example 0.7 mm thick, to form a mini-battery 20. The body is preferably pre-polished and has parallel faces.

[0041] Preferably, the liquid is heated to a certain temperature, for example 50° C., to speed up the process.

[0042] For LLZO-based compounds, the protonation equation with water is as follows: LLZO+H2O→HLLZO+LiOH

[0043] Regardless of the liquid used, protonated compounds of the HLLZO family are obtained, which are softer than the non-protonated LLZO family, which are very hard ceramics.

[0044] After this step, the body 11 has protonated layers 12, 13 around its periphery. The layers 12, 13 are deposited all around the periphery of the body 11 when the body is fully immersed in the liquid.

[0045] The layers have a thickness of, for example, 20 μm. The first layer 13 is deposited on a first side 7 of the body 11 and the second layer 12 is deposited on a second side 9 of the body 11 .

[0046] The method 10 includes a second step 2 of removing the second protonated layer 12 from the second side 9 of the body 11 so that in the next step, the positive electrode 15 can be directly laminated onto the non-protonated portion of the body 11. This is because the conductivity between the positive electrode 15 and the non-protonated portion is better than between the positive electrode 15 and the protonated portion.

[0047] Preferably, the second removal step 2 includes polishing the second side 9 of the body 11. Polishing removes the protonated layer of material 12 and exposes the unprotonated portion of the body 11. For example, a 600 grit abrasive is used to remove the HLLZO-based protonated layer.

[0048] In the third step 3, the body 11 is heated to a predetermined temperature in order to remove impurities from the body 11. The predetermined temperature is preferably 300-500°C, preferably 350-450°C. This temperature range prevents denaturation or decomposition of the material of the body 11, regardless of whether it is protonated or not. In particular, carbonate-type molecules increase the resistance at the interface between the electrode and the electrolyte, and therefore it is desired to remove them from the surface of the body 11. The heating time is, for example, about 3 hours.

[0049] A fourth step 4 consists of depositing metal elements forming the negative electrode 14 on the protonated portion on the first side of the body 11. The first side 7 is chosen to be opposite the second side 9 of the body 11. Thus, the body 11 has a positive electrode 15 on one side and a negative electrode 14 on the other side.

[0050] The metallic element includes a material selected from the following: - Alkali metals such as lithium, sodium, potassium, rubidium, cesium, or francium, - alkaline earth metals such as beryllium, magnesium, calcium, strontium, barium, or radium, - all transition metals from groups 3 to 11 of the periodic table, including the lanthanides and actinides, - Alloys of these metals.

[0051] The metallic element is preferably made entirely of this material.

[0052] Preferably, lithium is selected for its physical and chemical properties that lend themselves to use as the negative electrode 14 .

[0053] The molten metal element is deposited on the first protonated side 7 of the body 11, i.e., the metal element is deposited in a molten state on the first side 7. In this state, the metal element adheres to the first side 7 of the body 11, in particular maximizing the contact surface area between the metal element and the body 11.

[0054] The method includes a fifth step 5 of attaching a positive electrode 15 to a second side 9 of the body 11 opposite the negative electrode 14, the second side 9 having been polished and not protonated as in the second step 2.

[0055] For this purpose, a polymeric adhesive 16 is used to combine these, called the cathode liquid, so that the adhesive 16 becomes an ion conductor, allowing ions to pass through.

[0056] For example, a polymer adhesive 16 containing PEO-based polyethylene oxide, LiTFSi (lithium bis(trifluoromethanesulfonyl)imide)-based lithium salt, and THF (tetrahydrofuran) is used. The polymer adhesive 16 is dissolved in THF (tetrahydrofuran) and then laminated onto the second side 9, for example, using a drop-cast method. The THF is then dried, and the positive electrode 15 is laminated onto the polymer adhesive 16 such that the positive electrode 15 is permanently adhered to the second side 9.

[0057] The positive electrode 15 contains, for example, a material selected from the following: - LiNi x Mn y Co z O2 or Li 2-x-y-z Ni x Mn y Co z Lithium nickel manganese cobalt oxide (NMC) such as O2, where x+y+z≦1, - LiNi 0.5 Mn 1.5 Lithium nickel manganese oxide (LNMO) such as O4, - Lithium iron phosphate (LFP) such as LiFePO4, - LMO-based lithium manganates such as LiMn2O4, and - NCA-based lithium nickel cobalt aluminum oxides such as LiNiCoAlO2.

[0058] The positive electrode 15 is preferably made predominantly from this material, in combination with a polymeric binder and carbon to improve their ionic and electronic conductivity.

[0059] The sixth step 6 consists of forming dendrites 18 in the remaining protonated layer 13 from the metallic elements of the negative electrode 14. The dendrites 18 are elongated elements that penetrate into the protonated layer 13, which is weaker than the non-protonated part 11. The dendrites 18 form spontaneously due to the flow of electric current. Cracks form in the protonated layer 13, which are then filled with metallic elements from the negative electrode 14.

[0060] Thus, the sixth step 6 involves successive repetitions of current flow cycles between the negative electrode 14 and the positive electrode 15. During each cycle, a current is applied to the battery terminals, the negative electrode 14 and the positive electrode 15. The current may be, for example, 0.1 mA / cm 2 is selected so that

[0061] Over the course of several cycles, preferably less than 10, the polarity of the current changes: a positive current is followed by a negative current and vice versa.

[0062] Dendrites 18, preferably of lithium, penetrating the protonated layer 13 increase the contact area between the negative electrode 14 and the solid electrolyte 8, thereby improving the quality of the ionic contact.

[0063] Figure 2a) shows a body 11 made entirely of LLZO-based ceramic material. After a first protonation step, the body 11 comprises protonated layers 12, 13 around its periphery, as shown in figure 2b). The first layer 13 is disposed on a first side 7 of the body 11 and the second layer 12 is disposed on a second side 9 of the body 11.

[0064] The second side 9 of the body 11 is then polished so as to expose the unprotonated portion of this side, resulting in the body 11 in FIG. 2c) having an unprotonated portion on the second side 9 and a protonated layer 13 on the first side 7 of the body 11.

[0065] According to a fourth step, as shown in FIG. 2d), a negative electrode 14 is formed by depositing a molten metal element, preferably lithium, on the first protonated side 7 of the body 11. The body 11 remains substantially the same after the fifth removal step.

[0066] As shown in FIG. 2 e ), a positive electrode 15 is attached to the second, non-protonated side 9 of the body 11 using a polymer adhesive 16 .

[0067] FIG. 2f) shows a sixth step of dendrite formation, in which a current is applied cyclically to the negative electrode 14 and the positive electrode 15 of the battery using a current generator 19. It can be seen that dendrites 18 have formed in the cracks of the protonated layer 13 of the body 11. These dendrites 18 are blocked by the non-protonated parts of the body 11, which are harder than the protonated layer 13.

[0068] Dendrites 18 are elongated elements that extend from negative electrode 14 to protonation layer 13 .

[0069] Thus, the battery 20 comprises an electrolyte 8 with a positive electrode 15 on either side and a negative electrode 14 on the other side, and a body 11 having overlapping protonated ceramic layers 13 and unprotonated portions.

[0070] Such a battery 20 can be used in any electronic system, such as a wristwatch or pocket watch, a drone, a mobile phone, a laptop computer, or an electric vehicle, in which case the battery would of course be of large size.

[0071] Of course, the invention is not limited to the embodiments described with reference to the figures, and alternatives are contemplated without departing from the scope of the invention. [Explanation of symbols]

[0072] 1. First Step 2. Second step 3. Third step 4. Fourth step 5. The Fifth Step 6. Sixth Step 7. First aspect 8 Solid electrolyte 9. The Second Aspect 10. Production methods for solid-state batteries 11 Main unit 12 Protonated Layer 13 Protonated Layer 14 Negative electrode 15 Positive electrode 16 Polymer Adhesives 18 Dendrite 19 Current Generator 20 batteries

Claims

1. A method (10) for producing a solid-state battery (20) having a solid electrolyte (8), comprising the following successive steps: - protonating a body (11) containing a protonatable ceramic material to form a protonated layer (12, 13) on said body (11); - depositing (4) metallic elements forming a negative electrode (14) on said protonation layer (13) on a first side (7) of said body (11); - attaching (5) a positive electrode (15) to the second side (9) of said body (11); and - forming dendrites (18) in the protonated layer (13) of the body (11) from metallic elements of the negative electrode (14) (6); Including, 20. The method of claim 19, wherein the step (6) of forming the dendrites (18) comprises successively repeating cycles of current flow between the negative electrode (14) and the positive electrode (15), and the increased contact area between the negative electrode (14) and the solid electrolyte (8) via the dendrites (18) improves the quality of the ionic contact.

2. The ceramic material is doped or undoped lithium and / or lanthanum zirconium oxides of the LLZO system, - doped or undoped β-alumina solid electrolyte materials, - Li 6 P.S. 5 X-based (X is selected from the elements Cl, Br, or I) or Li 2 S-P 2 S 5 sulfide-based solid electrolyte materials, - Li 3 M.X. 6 (M is a metal or a metal alloy, and X is a halogen) - Lithium ion conductive solid electrolyte materials based on LISICON (lithium superionic conductor), and - NASICON (sodium superionic conductor) based sodium ion conductive solid electrolyte material 2. The method (10) according to claim 1, characterized in that the material is selected from the group consisting of:

3. A method (10) according to claim 1 or 2, characterized in that in the protonation step (1), the body (11) is immersed in a protic or acidic solvent, such as water, acetone, mineral oil or ethanol.

4. The method (10) according to claim 1 or 2, characterized in that it comprises an additional step (3) of heating the body (11) to a predetermined temperature in order to remove impurities from the body (11), said predetermined temperature being between 350 and 450°C, and that the heating step (3) precedes the step (4) of depositing the metallic elements.

5. 3. A method (10) according to claim 1 or 2, characterized in that said metal elements are melted onto said body (11) during said metal element deposition step (4).

6. The metal element is - the alkali metals lithium, sodium, potassium, rubidium, cesium or francium, - the alkaline earth metals beryllium, magnesium, calcium, strontium, barium or radium; - all the transition metals from groups 3 to 11 of the periodic table, including the lanthanides and actinides, and - Alloys of these metals 3. The method (10) according to claim 1 or 2, characterized in that it contains a substance selected from the group consisting of:

7. 3. The method (10) according to claim 1 or 2, characterized in that it comprises an additional step (2) of removing a portion of the protonated layer (12) from the body (11) in order to deposit the positive electrode (15) directly on the non-protonated part (11) of the body.

8. 8. The method (10) of claim 7, characterized in that the additional step (2) of removing a portion of the protonated layer from the body (11) is performed by polishing the second side (9) of the body (11).

9. The positive electrode (15) is - Lithium nickel manganese cobalt oxide of the NMC series, - lithium nickel manganese oxide of the LNMO series, - lithium iron phosphate of the LFP series, - LMO-based lithium manganates, and - NCA-based lithium nickel cobalt aluminum oxide 3. The method (10) according to claim 1 or 2, characterized in that it contains a material selected from:

10. 1. A solid-state battery (20) having a negative electrode (14), a positive electrode (15), and a solid electrolyte (8) including a solid ceramic electrolyte (8), the solid electrolyte (8) being provided with a protonated layer (13) and a non-protonated portion superimposed thereon, the positive electrode (15) being laminated on a body (11), the negative electrode (14) comprising a metal element laminated on the protonated layer (13) of the body (11) on the side opposite to the positive electrode (15), the metal element comprising a dendrite (18) penetrating the protonated layer (13) of the body (11), an increase in the contact area between the negative electrode (14) and the solid electrolyte (8) via the dendrite (18) improving the quality of ionic contact, and the material of the solid ceramic electrolyte (8) being a doped or undoped beta alumina solid electrolyte material.

11. 11. A solid-state battery (20) having a solid electrolyte (8) according to claim 10, characterized in that the dendrites (18) are blocked by non-protonated parts of the body (11).

12. The metal element is - the alkali metals lithium, sodium, potassium, rubidium, cesium or francium, - the alkaline earth metals beryllium, magnesium, calcium, strontium, barium or radium; all the so-called transition metals of groups 3 to 11 of the periodic table, including the lanthanides and actinides, - Alloys of these metals 12. A solid-state battery (20) having a solid electrolyte (8) according to claim 10 or 11, characterized in that it contains a material selected from the group consisting of:

13. 12. A solid-state battery (20) having a solid electrolyte (8) according to claim 10 or 11, characterized in that the positive electrode (15) is joined to the non-protonated part of the body (11).

14. The positive electrode (15) is - Lithium nickel manganese cobalt oxide of the NMC series, - lithium nickel manganese oxide of the LNMO series, - lithium iron phosphate of the LFP series, - LMO-based lithium manganates, and - NCA-based lithium nickel cobalt aluminum oxide 12. A solid-state battery (20) having a solid electrolyte (8) according to claim 10 or 11, characterized in that it contains a material selected from the group consisting of:

15. 12. An electronic system, a watch, a laptop computer, a mobile phone or a car comprising a solid-state battery (20) having a solid electrolyte (8) according to claim 10 or 11.

Citation Information

Patent Citations

  • Thin film lithium battery

    JP1984226472A

  • Stabilized solid garnet electrolyte and method

    JP2018502809A

  • Composite structure, lithium battery, and method for manufacturing composite structure

    JP2020077571A

  • System and method for treating the surface of a solid electrolyte

    JP2020516028A

  • Solid secondary battery

    JP2022148439A